2001
DOI: 10.1097/00005768-200110000-00020
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of change in &OV0312;O2max and maximal heart rate in master athletes

Abstract: In conclusion, these data suggest that VO2max declines in male and female master athletes at a rate similar to or greater than that expected in sedentary older adults. Additionally, these data suggest that maintenance of LBM and VO2max were associated in men, whereas in women, estrogen replacement and maintenance of training volume were associated with maintained VO2max.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 17 publications
5
83
0
3
Order By: Relevance
“…An age-related reduction in VO 2max has also been well documented in both cross-sectional and longitudinal studies of male and female endurance athletes undertaking high levels of endurance training into older age [11,32,40,42,48,53,56,57,71,72,78,106,108], suggesting that some decrease in VO 2max appears inevitable with aging, despite physical training into older age. However, the rates of decline in VO 2max have been reported to be reduced [54,55,78], similar [108], or greater [47,71] than age-matched sedentary individuals.…”
Section: Maximal Aerobic Powermentioning
confidence: 97%
See 1 more Smart Citation
“…An age-related reduction in VO 2max has also been well documented in both cross-sectional and longitudinal studies of male and female endurance athletes undertaking high levels of endurance training into older age [11,32,40,42,48,53,56,57,71,72,78,106,108], suggesting that some decrease in VO 2max appears inevitable with aging, despite physical training into older age. However, the rates of decline in VO 2max have been reported to be reduced [54,55,78], similar [108], or greater [47,71] than age-matched sedentary individuals.…”
Section: Maximal Aerobic Powermentioning
confidence: 97%
“…-maximal O 2 consumption (VO 2max ) -maximal heart rate -stroke volume -lactate threshold -economy of movement -muscle fiber type, morphology and capillarization -aerobic enzyme activity Apart from these above factors, previous research suggests that both muscle mass [47,73] and blood volume [23,25,89] may affect endurance performance in masters athletes. Thus, within this review, each of the above factors will be discussed, including:…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular system, as a vital blood and oxygen delivery system, is one key factor affecting an individual's capacity to perform physical work. The maximal heart rate has been reported to decline approximately 3-5 % per decade regardless of sex or exercise activity (Hawkins et al 2001;Trappe et al 1996). Also, more peripheral changes in aging contribute to the decline in aerobic capacity.…”
Section: Agingmentioning
confidence: 99%
“…Since skeletal muscles are one of the main tissues utilizing oxygen during exercise performance, changes in body composition are evident in aerobic capacity at the whole-body level. Former studies have established a link between lean body mass and VO2max in both men and women (Toth et al 1994;Hawkins et al 2001;Rosen et al 1998).…”
Section: Agingmentioning
confidence: 99%
“…Sport scientists [19,49,50] have suggested that prolonged training by Masters athletes plays a critical role in the maintenance of athletic performance even in the face of predicted agerelated decline. The physiological changes that occur with age are well documented-age changes for maximal heart rate [51] and aerobic capacities [52][53][54] are significant. Yet, age-related physiological decline is not as severe in Masters athletes.…”
Section: Qualities Related To Sport Participation In Youthmentioning
confidence: 99%